Functional outcomes of patients in ICU using the Chelsea Critical Care Physical Assessment tool: An integrative review - Lebogang C. Tjale; Silmara Hanekom; Nombeko Mshunqane (AOSIS, 2023)
Background: Outcome measures can assess the change in the health status of a patient in an intensive care unit (ICU). The Chelsea Critical Care Physical Assessment (CPAx) tool is used to assess the functional outcomes to monitor patient progression or regression in an ICU. Objectives: Our study aimed to identify studies that assess the functional outcomes of patients nursed in ICUs that use the CPAx tool. Method: An integrative review framework was used. Data were analysed in five steps to formulate a conclusion that aligned with the objective of our study. Data were extracted from peer-reviewed articles published online between 2013 and 2022. Databases that were used include Google Scholar, Directory of Open Access Journals (DOAJ) and PubMed for reviewed articles. Keywords were used in the search strategy, and screening of abstracts was done to extract studies that met the inclusion criteria. Results: We retrieved 41 studies, of which 11 matched the inclusion criteria. Data were thematically arranged into studies measuring the validity and reliability of the CPAx tool, using the CPAx tool to measure outcomes in the ICU, the tool used at ICU and hospital discharge. Conclusion: The use of the CPAx tool has no impact on measuring the hospital length of stay or quality of life. Clinical implications: The tool is comprehensive and enhances the accuracy of patient assessment.